QUE RAP É ESSE? QUE EU QUERO ESCREVER! Reflexões historiográficas sobre o movimento Hip Hop em Mato Grosso do Sul - Matheus Firmino Leite (2024)
This work aims to contribute to the studies that have been recognized as part of the Hip-hop Studies enterprise and presents a set of partial reflections carried out with the aim of establishing consistent historiographical reflections on the History and historiography of Hip Hop in the Afro-Atlantic diaspora. The texts are taken as historical sources that inform the self-referential narratives of the Hip Hop movement and culture. In the firstvpart of the text we articulate digital sources published on the websites Rap Dab (rapdab.com.br) and Campo Grande News (campograndenews.com.br) that demonstrate the narrative polyphony of Hip Hop as a specific challenge to historiography. In the second chapter, starting from a post-critical framework, we analyze how rapper Rincon Sapiência inscribes ambivalent notions about black masculinity in his debut album Galanga Livre (2017), referencing a particular discourse about blackness and diaspora.